Indonesian Women’s Rowing from 1986 to 2018: A historical, Social, and Cultural Perspective - Dede Rohmat Nurjaya; Amung Ma’mun; Agus Rusdiana (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2020)
In 1954, the International Federation of Societes d'Aviron (FISA) organized the first European women's rowing championship in Macon, France. Female rowing athletes around the world had actively participated for years, competing not only in local and national competitions, but also in international level. Apart from the historical evidence that women could indeed compete at the international level, the FISA delegation found it more appropriate to limit women's international participation by shortening the distance of women's competitions to half of male athletes and limiting the number and the type of race. Although women's international athletes were limited, the introduction of women's races at European championships created opportunities for female athletes to show their abilities to the public while challenging social and historical discourse about Indonesian women's participation in rowing. Eversince this first race, female athletes and coaches had a desire to achieve gender equality in sports that are usually associated with men and masculinity. In 2003, their efforts culminated with the acceptance of women at European Championships, World Championships, and the Olympics, the change in the distance of women's rowing from 1,000 meters to 2,000 meters, and the introduction of women's lightweight class at World Championships and the Olympics. This study examined the complex negotiations that had taken place since 1986 when Indonesian women's first rowing participated in the 1986 Asian Games until 2018 through collecting data from archival material and in-depth interviews, with current and previous athletes and coaches, to document and to examine the history of Indonesian women's involvement in rowing sports between 1987 and 2018.